2004
DOI: 10.1038/nn1197
|View full text |Cite
|
Sign up to set email alerts
|

Music, language and meaning: brain signatures of semantic processing

Abstract: Semantics is a key feature of language, but whether or not music can activate brain mechanisms related to the processing of semantic meaning is not known. We compared processing of semantic meaning in language and music, investigating the semantic priming effect as indexed by behavioral measures and by the N400 component of the event-related brain potential (ERP) measured by electroencephalography (EEG). Human subjects were presented visually with target words after hearing either a spoken sentence or a musica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
352
2
24

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 441 publications
(403 citation statements)
references
References 24 publications
25
352
2
24
Order By: Relevance
“…Using chord sequences, either consonant or dissonant, as priming stimuli, it was shown [21] that target words are faster recognized for emotionally congruent chord-word pairs than for incongruent ones. Further, when target words are preceded by semantically unrelated musical primes, N400, an ERP component reflecting contextual integration, effect is reported [12]. Altogether, this suggests that music has an excellent potential to be used as an emotional priming stimulus.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Using chord sequences, either consonant or dissonant, as priming stimuli, it was shown [21] that target words are faster recognized for emotionally congruent chord-word pairs than for incongruent ones. Further, when target words are preceded by semantically unrelated musical primes, N400, an ERP component reflecting contextual integration, effect is reported [12]. Altogether, this suggests that music has an excellent potential to be used as an emotional priming stimulus.…”
Section: Introductionmentioning
confidence: 82%
“…In other words, can music be used as an affective priming stimulus which could systematically influence the emotional processes of target visual stimuli? Music was earlier used as a priming stimulus in semantic context [12,21]. To the best of our knowledge, the current study is the first to address this issue in a crossmodal context by using both behavioural and ERP experiments.…”
Section: Introductionmentioning
confidence: 94%
“…A long history of dissociation between aphasia and amusia from the clinical neurology suggested that there are differences in the ways music and language are implemented by the brain, and modern brain imaging work has partially confirmed this finding. To the extent that music really requires a different suite of mechanisms from language, this is prima facie evidence against its being a spandrel of language (Peretz & Hyde, 2003;Peretz & Zatorre, 2005) but the considerable overlap between brain regions involved in musical and lingustic tasks currently offers no clear verdict on this question at present (Koelsch et al, 2002(Koelsch et al, , 2004Patel, 2003;Peretz & Zatorre, 2003). Another approach is to seek evidence that musical and linguistic skills are dissociated among individuals in a population, and that these differences have a genetic basis.…”
Section: Music As a Spandrelmentioning
confidence: 99%
“…Although Koelsch et al [2004] argues in favor of a greater role for musical semantics, there is certainly no dictionary of symbols and designates as exists for spoken language. Given a musician's special set of long-term experiences with listening to and creating a set of sounds (their ''listening biography''), we ask whether neural sensitivity reflects not only IBE combinations that are typically communication-relevant, but also distinct IBE combinations that have become relevant across the course of this extensive history.…”
Section: Introductionmentioning
confidence: 99%